SIDH: A Game-Based Architecture for a Training Simulator. (2nd February 2009) - Backlund, P.; Engström, H.; Gustavsson, M.; Johannesson, M.; Lebram, M.; Sjörs, E.
Abstract : Game-based simulators, sometimes referred to as "lightweight" simulators, have benefits such as flexible technology and economic feasibility. In this article, we extend the notion of a game-based simulator by introducing multiple screen view and physical interaction. These features are expected to enhance immersion and fidelity. By utilizing these concepts we have constructed a training simulator for breathing apparatus entry. Game hardware and software have been used to produce the application. More important, the application itself is deliberately designed to be a game. Indeed, one important design goal is to create an entertaining and motivating experience combined with learning goals in order to create a serious game. The system has been evaluated in cooperation with the Swedish Rescue Services Agency to see which architectural features contribute to perceived fidelity. The modes of visualization and interaction as well as level design contribute to the usefulness of the system.